Intra-operative cell salvage in obstetrics: are we good at it?. (18th April 2012) - Skeldon, R; Patravali, N; Lynch, P
Abstract : Introduction: Intra-operative cell salvage (IOCS) is the process where blood shed within the surgical field is collected, washed and pumped into an infusion bag for autologous transfusion. In Obstetrics it is used sparsely due to concern about contamination by amniotic fluid and fetal blood cells. Use of modern leucocyte depletion filters is effective at removing such contamination. The latest recommendation is for its use in cases of major obstetric haemorrhage involving blood loss > 1500 millilitres. Aim: The aim of our study was to find if there was adequate usage of cell salvage in obstetric cases. Method: Retrospective study. The data was collected from computer records and clinical notes for a period of 2 years. Data on Haemonetics Cell Saver 5 cell salvage machine was assessed. Results: There were 213 major obstetric haemorrhages in this time. Blood was collected via the cell salvage apparatus in 53 patients undergoing either Elective caesarean section (57%) or Emergency caesarean section (43%). Autologous transfusion was carried out in 8 of these patients (15%). One patient had a minor postoperative complication unrelated to transfusion. Conclusion: IOCS is inadequately used in obstetrics. Re-transfusion rates were poor due to inadequate volumes collected. There were no major complications in patients receiving transfusion. Recommendations: Increasing training opportunities for all staff is necessary for adequate implementation of IOCS. Early decision to use IOCS, especially in anticipated elective or emergency procedures may allow adequate collection of blood for re-transfusion. Re-audit following staff training will be useful to assess clinical practice.